Transformasi Kehidupan Paulus oleh Roh Kudus: Studi Hermeneutika Kisah Para Rasul 9:17 - Estefanus, Christopher Sigar; Manurung, Kosma (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: Conversion and being newly born is a spiritual experience closely connected with the encounter with the Holy Spirit. The story of Saul's conversion is popular in the Bible. Starting with his miraculous encounter with Jesus when Saul was on his way to Damascus and then his encounter with Ananias who God sent through a vision to meet Saul. A conversion story that is best framed in Acts 9:17. Through the recorded experience of Paul in this text, readers will get the idea of the Holy Spirit’s work as a guide to someone’s conversion. This research aims to analyze the real role of the Holy Spirit in Paul's conversion process in convincing him about the lives of believers today. The reason and main background of this study is the author’s curiosity to deeply understand about how the Holy Spirit work in conversion of a believer. The method chosen to work on this article is descriptive qualitative and literature review. This article further discusses the story of Paul's conversion, including several important events that started it and the role of the Holy Spirit in conversion, which also has an influence on the present. It is concluded that the Holy Spirit is not only the main factor in a person's conversion but also plays an active role in modifying him into a new person and equipping him to become a tool in preaching the good news. Abstrak: Pertobatan dan kelahiran baru merupakan sebuah pengalaman spiritual yang tidak terpisahkan dari perjumpaan seseorang dengan Roh Kudus. Kisah pertobatan Paulus adalah sebuah kisah yang populer dalam Alkitab. Dimulai dengan perjumpaannya yang ajaib dengan Yesus ketika Paulus sedang dalam perjalanan menuju Damsyik lalu perjumpaannya dengan Ananias yang diutus Tuhan melalui suatu penglihatan untuk berjumpa dengan Paulus. Sebuah kisah pertobatan yang terbingkai dengan sangat baik dalam Kisah Para Rasul 9:17. Melalui pengalaman Paulus yang terekam dalam teks ini, para pembaca dapat memperoleh gambaran bagaimana Roh Kudus bekerja menuntun seseorang untuk bertobat. Tujuan dilakukannya penelitian ini adalah untuk menganalisa peran nyata dari Roh Kudus dalam proses pertobatan Paulus dalam implikasinya terhadap kehidupan orang percaya masa kini. Alasan dan latar belakang utama yang melandasi penelitian ini adalah keinginan peneliti untuk memahami lebih dalam tentang bagaimana Roh Kudus berperan dalam pertobatan seseorang. Metode yang dipilih untuk mengerjakan artikel ini adalah kualitatif deskriptif dan kajian literatur. Lebih jauh artikel ini kemudian membahas tentang kisah pertobatan Paulus dengan beberapa peristiwa penting yang mengawalinya, peran Roh Kudus dalam pertobatan, juga implikasi pada masa kini. Disimpulkan bahwa, Roh Kudus bukan sekedar faktor utama pertobatan seseorang melainkan juga berperan aktif dalam mengubahnya menjadi manusia baru serta memperlengkapinya untuk menjadi alat dalam pemberitaan kabar baik.